Mental health interventions in the mining industry: a narrative review. Issue 2 (27th May 2020) - Asare-Doku, Winifred; Rich, Jane; Kelly, Brian; James, Carole
Abstract : Purpose: Previous research has suggested high levels of unaddressed mental health needs among male-dominated work settings. The mining industry has been a recent focus internationally. This paper aims to critically examine research regarding organizational mental health interventions for people working in mining industries. Design/methodology/approach: The narrative review used a systematic standardized search strategy in six databases and grey literature from 1990 to 2019. Findings: Of the 418 studies identified, seven studies (five quantitative and two qualitative studies) met the inclusion criteria. Analysis of these studies revealed the organisational interventions available to address mental health needs of miners. Interventions were categorised into organisational and individual-focused approaches. Evidence shows there is great potential in conducting workplace mental health programs, yet further research is required to create a strong evidence base for substantiated policy and practice implications. Practical implications: Mental health interventions and programs should be available in mining industry to enhance mental health. Organisations can also improve mental health by implementing significant changes in the work environment and identifying workplace factors that induce strain and contribute to psychological distress in employees. Attempt can be made at restructuring safety policies and practices to include mental health, addressing organisational structures such as work schedules and providing training for managers and supervisors. Originality/value: This review focuses on the unique characteristics pertaining to male-dominated mining industries and workplace mental health interventions which are aimed at supporting employee mental health.